That's So Last Season: Unraveling the Genomic Consequences of Fur Farming in Arctic Foxes ( Vulpes lagopus ) - Christopher A. Cockerill; J. Camilo Chacón‐Duque; Nora Bergfeldt; Johanna von Seth; Gabriella Björklund; Malin Hasselgren; Johan Wallén; Anders Angerbjörn; Eva Fuglei; Ester Rut Unnsteinsdottir; Paula White; Gustaf Samelius; et al. (Molecular Ecology, 2025)
Humans have relied on animal fur for centuries, yet fur farming only began recently during the mid‐19th Century. Little is known about this incipient domestication or the genomic processes involved. Domestication may involve founder effects, population bottlenecks and low population size, which, when combined with intense artificial selection, lead to inbreeding, a limited gene pool and reduced fitness. The arctic fox ( Vulpes lagopus ) has been farmed intensively since the early 1900s and has been artificially selected for economic phenotypes. We investigated the origin of these lineages and the genomic consequences of intensive farming by comparing the genomes of farmed and wild arctic foxes from across their range. Our research indicates recent inbreeding through long Runs of Homozygosity and reduced genomic variation in farmed foxes relative to their respective wild populations. We identified a coastal ecotype origin for all Fennoscandian farmed arctic foxes, aligning them phylogenetically with the wild Icelandic population, a geographically isolated and phenotypically distinct coastal lineage. The depleted genome‐wide heterozygosity and increased recent inbreeding in farmed fox lineages is consistent with a heavy consequence of domestication, shedding light on the demographic history and genomic consequences of human manipulation. We highlight the need for increased genomic investigations into fur farm populations to understand the incipient domestication process and uncover the cost of intense farming. The genomic consequences of domestication must be considered in the management of fur farms, with actionable steps needed to prevent descendants of escaped farmed foxes from polluting the gene pool in the wild through introgression.

The petrology and geochemistry of the Montagna Grande-Monte Gibele trachytic shield volcano (Pantelleria, Italy) - John C. White; Ray Macdonald; Pierangelo Romano; Bogusław Bagiński; Silvio G. Rotolo; Beata Marciniak-Maliszewska; Alessandra Cinquegrani (Geochemistry, 2025)

Life history strategies determine response to SRT driven crash in anammox bioreactors - Christian A. White; Edmund H. Antell; Sarah L. Schwartz; Jennifer E. Lawrence; Ray Keren; Lijie Zhou; Ke Yu; Wei-Qin Zhuang; Lisa Alvarez-Cohen (Water Research, 2025)

Single-crystal 40Ar/39Ar dating of the Montagna Grande-Monte Gibele trachytic shield volcano, Pantelleria (Strait of Sicily rift zone), Italy - John C. White; Daniel P. Miggins; Ray Macdonald (Geochemistry, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Peralkaline felsic magmatism at the Nemrut volcano, Turkey: impact of volcanism on the evolution of Lake Van (Anatolia) IV - Ray Macdonald; Mari Sumita; Hans-Ulrich Schmincke; Bogusław Bagiński; John C. White; Sławomir S. Ilnicki (Contributions to Mineralogy and Petrology, 2015)

Forage radish and cereal rye cover crop effects on mycorrhizal fungus colonization of maize roots - Charles M. White; Ray R. Weil (Plant and Soil, 2010)

Stratification by CARD15 variant genotype in a genome-wide search for inflammatory bowel disease susceptibility loci - Sarah H. Shaw; Jochen Hampe; Ray White; Christopher G. Mathew; Mark E. Curran; Stefan Schreiber (Human Genetics, 2003)

The identical 5? splice-site acceptor mutation in five attenuated APC families from Newfoundland demonstrates a founder effect - Lisa Spirio; Jane Green; Jennifer Robertson; Margaret Robertson; Brith Otterud; John Sheldon; Erica Howse; Roger Green; Ray White; Mark Leppert; Joanna Groden (Human Genetics, 2000)

Duchenne/Becker muscular dystrophy: correlation of phenotype by electroretinography with sites of dystrophin mutations - De-Ann M. Pillers; K.M. Fitzgerald; N.M. Duncan; S.M. Rash; R.A. White; S.J. Dwinnell; B.R. Powell; R.E. Schnur; P.N. Ray; G.W. Cibis; R.G. Weleber (Human Genetics, 1999)

Duchenne/Becker muscular dystrophy: correlation of phenotype by electroretinography with sites of dystrophin mutations - De-Ann M. Pillers; K.M. Fitzgerald; N.M. Duncan; S.M. Rash; R.A. White; S.J. Dwinnell; B.R. Powell; R.E. Schnur; P.N. Ray; G.W. Cibis; R.G. Weleber (Human Genetics, 1999)

A study of genetic diversity in Populus nigra subsp. betulifolia in the Upper Severn area of the UK using AFLP markers - M. O. WINFIELD; G. M. ARNOLD; F. COOPER; M. LE RAY; J. WHITE; A. KARP; K.J. EDWARDS (Molecular Ecology, 1998)
A survey of amplified fragment length polymorphism (AFLP) was conducted to examine genetic diversity in 146 individuals of British, native black poplar ( Populus nigra subsp. betulifolia ) and three individuals considered by collectors to be non‐ betulifolia poplars. Using two primer pairs, a total of 147 bands were detected of which 82 (56%) were polymorphic in at least one individual. Cluster analysis and principal coordinates analysis of the calculated similarity matrix revealed a low level of genetic diversity, although a loose clustering into five groups could be identified, one of which contained the non‐ betulifolia individuals. Examination of the spatial distribution of the other four groups (all betulifolia ) revealed a general correlation between geographic proximity and genetic similarity. On the basis of the polymorphism observed, it was possible to identify a small number of individual plants which exhibit maximum diversity and might therefore be suitable for inclusion in a replanting programme designed to maintain at least the existing low level of polymorphism observed within British black poplar.